Carta Editorial - Dutra e Silva, Sandro; Miraglia, Marina; Ortega Santos, Antonio; Olivieri, Chiara; Olvera, Martha Micheline C.; Broto, Pablo Corral (Historia Ambiental Latinoamericana y Caribeña (HALAC) revista de la Solcha, 2019)
Carta Editorial